Experimental study on the thixotropic strength of the marine soft clay from the Yangtze River estuary - Wang, Binghui; Huang, Yanyu; Zhu, Enci; Xiao, Xing; Wu, Qi (Frontiers in Marine Science, 2024)
Soft clay in the offshore area of the Yangtze River estuary has been investigated considering its basic physical properties. Forty-five unconfined compressive strength tests were conducted on the remolded marine soft clay to investigate the impacts of curing time T, water content w, plasticity index IP, and clay particle content ρc on the thixotropic static shear strength ratio As of the marine soft clay from the Yangtze River estuary. Results show that the stress–strain curves were primarily strain hardening and strain softening curve types. Unconfined compressive strength qu increased with an increase in T. All specimens with different basic physical properties were capable of thixotropic strength recovery. When T = 0–28 days, As increased rapidly, while for T > 28 days, As of most specimens increased slightly or tended to stabilize. The impacts of w, IP and ρc on As do not follow a consistent pattern, but there is a strong correlation between As and w/wL (wL is the liquid-limit water content). For w/wL < 0.75, As increased with increasing w/wL, whereas for w/wL ≥0.75, As decreased with increasing w/wL. We proposed a simple and widely applicable power function prediction model for the As of the soft clay from the Yangtze River estuary.